Marula oil nanoemulsion improves motor function in experimental parkinsonism via mitigation of inflammation and oxidative stress - Reem Alshaman; Mona Qushawy; Mona Qushawy; Hatem I. Mokhtar; Angie M. Ameen; Rehab M. El-Sayed; Eman Saad Alamri; Lamiaa M. Elabbasy; Lamiaa M. Elabbasy; Ahmed M. N. Helaly; Walid F. Elkhatib; Walid F. Elkhatib; et al. (Frontiers Media S.A., 2023)
Introduction: Parkinson's disease (PD) is a neurologic condition exhibiting motor dysfunction that affects old people. Marula oil (M-Oil) has been used longley in cosmetics and curing skin disorders. M-Oil is particularly stable due to its high concentration of monounsaturated fatty acids and natural antioxidants. The current study formulated M-Oil in an o/w nanoemulsion (M-NE) preparations and tested its anti-inflammatory and antioxidant actions against experimental parkinsonism.Methods: Four experimental groups of male albino mice were used and assigned as vehicle, PD, PD + M-Oil and PD + M-NE. Locomotor function was evaluated using the open field test and the cylinder test. Striatal samples were used to measure inflammatory and oxidative stress markers.Results: The results indicated poor motor performance of the mice in PD control group then, improvements were recorded after treatment with crude M-Oil or M-NE. In addition, we found high expression and protein of inflammatory markers and malondialdehyde levels in PD group which were downregulated by using doses of crude M-Oil or M-NE. Hence, formulating M-Oil in form of M-NE enhanced its physical characters.Discussion: This finding was supported by enhanced biological activity of M-NE as anti-inflammatory and antioxidant agent that resulted in downregulation of the inflammatory burden and alleviation of locomotor dysfunction in experimental PD in mice.